Freedom of information - Krishna Iyer, V. R. (Lucknow, 1990)
This book contains a perspective and forceful exposition on one of the most basic and important right--the right to information. The work dwells on the realisation that without free access to information locked in government files by the outdated Official Secrets Act, the exercise of all other rights itself is endangered and liberty is never fully realised. The phenomenon is global, compounded by advancements in technology which have made surveillance, and data collection by the State very easy and thereby all the more pernicious. Never before was the need felt greater than now for a open and free society to secure which free and unhindered access to information is the desideratum. The author has travelled to all continents and compared the laws and situation in other free societies like the US, UK, Canada, Sweden and Australia etc., as well as the Soviet Union and argued on the different facets the urgency and need for openness. The study purports to illumine the dismal situation in India and make realisation of the freedom of information a reality.
Keywords: Freedom of Pree